Plant-ants use resistance-related plant odours to assess host quality before colony founding - Razo-Belman, Rosario; Molina-Torres, Jorge; Martínez, Octavio; Heil, Martin (The Journal of ecology, 2018)
1. Establishing a horizontally transmitted mutualism is a critical step for many organisms, particularly when an individual can engage with only one partner over its lifetime. Ant foundresses shed their wings before they start to lay eggs, which makes host choice particularly critical for plant-ants that exclusively colonize myrmecophytes. 2. Volatile organic compounds (VOCs) can indicate the identity and physiological condition of an individual and frequently serve as signals or cues that facilitate partner choice. Thus, we hypothesized that obligate plant-ants use VOCs to determine the quality of potential host plants. 3. Indeed, winged females of the plant-ant, Pseudomyrmex ferrugineus, used plant odours to identify high-quality acacia hosts among different species and among individuals of the same species. The VOC blend of a branch was related to reward production and, interestingly, the least attractive blend contained the highest number of compounds. 4. Although only seven different VOCs could be detected in the blend of the high-reward host species, the low-reward host emitted 13 different compounds, among which (S)-(-)-limonene and β-linalool were the dominant ones. Complementing the odour of the high-reward host with (S)-(-)-limonene, β-linalool or α-terpinene reduced its attractiveness. Strikingly, these compounds inhibited bacterial pathogens of the host plant. 5. Synthesis. Plant-ants can use host plant odours that contain resistance-related VOCs to judge on host quality, likely because of negative crosstalk between direct resistance to disease and investment in ant-mediated defence. VOCs can serve as cues that provide reliable information for partner choice, particularly when their emission results from a physiological process that causally relates to the quality of an individual as a mutualist.